Common Genetic Variant of INSIG2 Gene rs7566605 Polymorphism Is Associated with Severe Obesity in North India - Prakash, Jai (Iran Biomed J, 2017)
BACKGROUND: Obesity is a very common disorder resulting from an imbalance between food intake and energy expenditure, and it has a substantial impact on the development of chronic diseases. The aim of this study was to examine the association of INSIG2 (rs7566605) gene polymorphism with obesity and obesity associated phenotypes in North Indian subjects. METHODS: The variants were investigated for association in 642 obese and non-obese individuals. The genotyping of INSIG2 (rs7566605) single nucleotide polymorphism was analyzed by the TaqMan allelic discrimination protocol. RESULTS: A significant association was observed for INSIG2 (rs7566605) single nucleotide polymorphism with obesity and obesity-related phenotypes. Furthermore, a significant relationship was found between the rs7566605 and insulin, homeostasis model of assessment-insulin resistance, the percentage of body fat, fat mass, leptin, and adiponectin. CONCLUSION: The present study observed significant association between INSIG2 (rs7566605) single nucleotide polymorphism and obesity, as well as obesity-associated phenotypes in North Indian population.